Marginal bone resorption of posterior mandible dental implants with different insertion methods - Ehsan Aliabadi; Saeid Tavanafar; Mohammad Saleh Khaghaninejad (BMC, 2020)
Abstract Background To evaluated the marginal bone loss around dental implants by two insertion methods. Methods Eligible patients were divided into two groups; manual and mechanized groups. Peri-apical x-ray using a customized device to standardize the radiographs designed and used to take three periodical radiographs; after surgery, three months, and six months follow up. An independent t-test was used to compare the two groups regarding the average level of marginal bone loss (p < 0.05). Results After excluding dropouts, a total of 273 patients (120 males and 153 females, aged between 25 and 67 years old) were included in the study. The average marginal bone loss in the manual insertion method was 0.44 ± 0.84 mm, and 0.59 ± 0.20 mm, and for the mechanized method was 0.51 ± 0.20 mm and 0.67 ± 0.19 mm after three and six months, respectively. There was a significant difference in marginal bone loss after six months between the two groups(p < 0.001). However, no differences were observed after three months (p = 0.24). Conclusions Under the condition of this study, both techniques were safe and resulted in an acceptable amount of bone resorption; however, in the manual method, the less marginal bone loss occurred after six months.